Governance in the High North: Rhetoric vs reality in the Barents region - Bourmistrov, Anatoli; Johansen, Svein Tvedt (Lapin Yliopisto / University of Lapland, 2019)
Source at http://urn.fi/URN:NBN:fi-fe2019060618731 . This special issue of Barents Studies attempts to contribute to a better understanding of the role of local governance in strategic development of the High North, with examples from the Barents Region. The High North regions have gained increased attention for their natural resources (including fish, oil, gas, minerals, tourist destinations, new transport solutions, and digital infrastructure), for creating business potential, and for opportunities to fuel continuous global economic growth (AMAP 2017). National governments increasingly expect key institutional actors in High North regions to take the responsibility for managing those vast resources in order to further local and regional economic and social development.